Survival Strategic Buruh PTPN XII Sempol Ijen Bondowoso: Survival Strategies of Workers at PTPN XII Sempol Ijen Bondowoso - M.F. Hidayatullah (Fenomena, 2011)
The welfare of plantation workers has never been adequate, including at PTPN XII. The wages they receive are far below the regional minimum wage (UMR) set by the government. Despite this, they continue to survive and live the "destiny" experienced by their parents, and possibly even by their children and grandchildren in the future. The results of this qualitative research reveal that to address their economic shortcomings, PTPN XII workers have developed relatively creative survival strategies over time. This article will explore some of the strategies employed by PTPN XII Sempol Ijen Bondowoso plantation workers to sustain their livelihoods. Kesejahteraan buruh perkebunan tidak pernah memadai, termasuk di PTPN XII. Upah yang mereka terima jauh di bawah upah minimum regional (UMR) yang ditetapkan pemerintah. Meski demikian, mereka tetap bertahan dan menjalani "takdir" yang dirasakan oleh orang tua mereka, bahkan mungkin oleh anak dan cucu mereka kelak. Hasil penelitian kualitatif ini menunjukkan bahwa untuk memenuhi kekurangan ekonomi, buruh PTPN XII telah mengembangkan strategi bertahan hidup yang relatif kreatif selama ini. Tulisan ini akan mengungkap beberapa strategi yang dilakukan oleh buruh perkebunan PTPN XII Sempol Ijen Bondowoso dalam mempertahankan kehidupan mereka.